Selective activation of the transcription factor NFAT1 by calcium microdomains near Ca2+ release-activated Ca2+ (CRAC) channels. - Kar, P; Nelson, C; Parekh, A (2011)
NFATs are a family of Ca(2+)-dependent transcription factors that play a central role in the morphogenesis, development, and physiological activities of numerous distinct cell types and organ systems. Here, we visualize NFAT1 movement in and out of the nucleus in response to transient activation of store-operated Ca(2+) release-activated Ca(2+) (CRAC) channels in nonexcitable cells. We show that NFAT migration is exquisitely sensitive to Ca(2+) microdomains near open CRAC channels. Another Ca(2+)-permeable ion channel (TRPC3) was ineffective in driving NFAT1 to the nucleus. NFAT1 movement is temporally dissociated from the time course of the Ca(2+) signal and remains within the nucleus for 10 times longer than the duration of the trigger Ca(2+) signal. Kinetic analyses of each step linking CRAC channel activation to NFAT1 nuclear residency reveals that the rate-limiting step is transcription factor exit from the nucleus. The slow deactivation of NFAT provides a mechanism whereby Ca(2+)-dependent responses can be sustained despite the termination of the initial Ca(2+) signal and helps explain how gene expression in nonexcitable cells can continue after the primary stimulus has been removed.